2015
DOI: 10.1002/hrdq.21211
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Business Impact of Employee Learning: A View From the Professional Services Sector

Abstract: Although the HRD literature is fairly consistent in affirming the recognition that employee learning is critical to organizational performance, there has been little agreement about how best to demonstrate the contribution of employee learning to the organization's bottom line, with approaches varying from industry to industry and from organization to organization. Focusing on the professional services sector, an industry sector that has garnered little attention in terms of HRD measurement research, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…An explanation for the relative importance of being able to deal with externals might be due to the large number of owner‐managers that were currently innovating through the introduction of care farming: a typical social innovation (Hassink, Hulsink, & Grin, ). Research from large service‐industry firms confirms the importance of seizing learning opportunities from clients (Van Rooij & Merkebu, ).…”
Section: Discussionmentioning
confidence: 94%
“…An explanation for the relative importance of being able to deal with externals might be due to the large number of owner‐managers that were currently innovating through the introduction of care farming: a typical social innovation (Hassink, Hulsink, & Grin, ). Research from large service‐industry firms confirms the importance of seizing learning opportunities from clients (Van Rooij & Merkebu, ).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, to understand the broader applicability of the theorizations developed within this article it would be useful to ascertain whether, and if so how, the concepts operate in larger organizational settings. In deepening the contributions made by this present study, scholars should consider how the impact of the claimed “co‐direction” of learning upon idea generation may be measured (van Rooij & Merkebu, ). Importantly, in this regard the application of longitudinal methodologies may be useful in tracking the impact of CDL upon the production, and subsequent development, of ideas.…”
Section: Limitations and Recommendations For Researchmentioning
confidence: 97%
“…Creativity, innovation, and learning are central to organizational success (Allocca & Kessler, ; Chien, Lin, & Ya‐Hui Lien, ; Herrera, ; van Rooij & Merkebu, ). In a world increasingly dominated by knowledge work (Lund, Manyika, & Ramaswamy, ; McIver, Lengnick‐Hall, Lengnick‐Hall, & Ramachandran, ) and information flows, the management of these, often intangible, attributes takes on increasing importance (Jimenéz‐Jimenéz & Sanz‐Valle, ; Shipton, West, Dawson, Birdi, & Patterson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The review of articles showed that there is no shortage of assessment methods and tools, such as scales, questionnaires, and key performance indicators, that could potentially be used (e.g., Kim & Marsick, 2013;Kyndt et al, 2014;Srimannarayana, 2009), but there are no simple solutions or "best practices" that could be implemented without first being adapted to an organization. Rather, each method and tool needs to be developed, tested, and evaluated to ensure fit to the organizational context (Tootell et al, 2009;van Rooij & Merkebu, 2015). Despite the availability of such assessment methods and tools, it is often challenging to convincingly link competence development activities to specific outcomes.…”
Section: Table 2 (Continued)mentioning
confidence: 99%